TRANSLATING JOURNALISTIC MATERIALS IN SOCIO-POLITICAL CONTEXTS - Kasimova A. N.; Muhammatova G. (Bright Mind Publishing, 2025)
The article aims to show the characteristics of translating journalistic materials in socio-political contexts, using examples from English and Uzbek. The study used several methods, including observation, interpretation, and generalization, as well as contextual analysis. It also involved careful selection of real texts for analysis. The study found that when translating socio-political terms, translators need to focus on several important aspects. These include translating abbreviations, descriptive phrases, stylistic elements, socio-political terminology, idiomatic expressions, and informal language.
Keywords: Socio-political terms,media, journalism, public, borrowings, calque, cultural nuances, original context, politics, publiscistics.